Acipimox Administration With Exercise Induces a Co-feedback Action of the GH, PP, and PYY on Ghrelin Associated With a Reduction of Peripheral Lipolysis in Bulimic and Healthy-Weight Czech Women: A Randomized Study - Smitka, Kvido; Nedvidkova, Jara; Vondra, Karel; Hill, Martin; Papezova, Hana; Hainer, Vojtech (Frontiers in Endocrinology, 2019)
Objective: Anti-lipolytic drugs and exercise are enhancers of growth hormone (GH) secretion. Decreased circulating free fatty acids (FFA) have been proposed to exert ghrelin-GH feedback loop after administration of an anti-lipolytic longer-acting analog of nicotinic acid, Acipimox (OLB, 5-Methylpyrazine-2-carboxylic acid 4-oxide, molecular weight of 154.1 Da). OLB administration strongly suppresses plasma FFA during exercise. Neuroendocrine perturbations of the adipose tissue (AT), gut, and brain peptides may be involved in the etiopathogenesis of eating disorders including bulimia nervosa (BN) and anorexia nervosa. BN is characterized by binge eating, self-induced vomiting or excessive exercise. Approach: To test the hypothesis that treatment with OLB together with exercise vs exercise alone would induce feedback action of GH, pancreatic polypeptide (PP), peptide tyrosine tyrosine (PYY), and leptin on ghrelin in Czech women with BN and in healthy-weight Czech women (HW). The lipolysis rate (as glycerol release) in subcutaneous abdominal AT was assessed with microdialysis. At an academic medical center, 12 BN and 12 HW (the control group) were randomized to OLB 500 mg 1 hour before a single exercise bout (45 min, 2 W/kg of lean body mass [LBM]) once a week vs identical placebo over a total of 2 weeks. Blood plasma concentrations of GH, PP, PYY, leptin, ghrelin, FFA, glycerol, and concentrations of AT interstitial glycerol were estimated during the test by RIA utilizing 125I-labeled tracer, the electrochemiluminescence technique (ECLIA) or colorimetric kits. Results: OLB administration together with short-term exercise significantly increased plasma GH (P<0.0001), PP (P<0.0001), PYY, and leptin concentrations and significantly decreased plasma ghrelin (P<0.01) concentrations in both groups, whereas short-term exercise with placebo resulted in plasma ghrelin (P<0.05) decrease exclusively in BN. OLB administration together with short-term exercise significantly lowered local subcutaneous abdominal AT interstitial glycerol (P<0.0001) to a greater extent in BN. Conclusion: OLB-induced suppression of plasma ghrelin concentrations together with short-term exercise and after the post-exercise recovering phase suggests a potential negative co-feedback of GH, PP, PYY and leptin on ghrelin secretion to a greater extent in BN. Simultaneously, the exercise-induced elevation in AT interstitial glycerol leading to a higher inhibition of peripheral lipolysis by OLB in BN.